Collected poems for children - Hughes, Ted, 1930-1998.; Briggs, Raymond (New York : Farrar, Straus and Giroux, 2008)
Collects more than 250 poems for children by poet laureate Ted Hughes, arranged by volume and age level, and includes nearly two hundred drawn illustrations.
Includes indexes.
Book Links (A.L.A.)
Booklist
School Library Journal
3-6.
Keywords: Children's poetry, English; English poetry; English poetry